Pentahelix Model-based Collaboration in the Implementation of Covid-19 Mitigation Policies - Rahmah, Laily Ainur; Nisa, Ainun; Kamil, Muhammad (Civiliza Publishing, 2025)
This study purpose to review and analyze the implementation policy to prevent Pandemic Covid-19 through pentahelix collaboration, using previous research as a reference source which is then analyzed to find out the urgency and differentiation between the research. From the results of previous research analysis, it can facilitate the author in understanding the phenomena and problems that happening in the implementation of the Covid-19 policy, so that it can make analyzed more specifically the role of the pentahelix collaboration in the implementation of policies, so as to produce the problem solving that can be used in the future. This study uses literature study method, in the form of journal, books, and other supporting documents. In addition, the study also used data obtained from the website of the drone emprit academic which contains the results of social media analysis, which is then reprocessed to be analyzed and narrated. This study refers to pentahelix model theory. So through this method and theory, it can be known that the results of the research is a collaboration conducted by the five pentahelix elements (government,society, academia,media, and private sector) still not implemented to the maximum. This was due to a lack of understanding of the policies made by the government in prevent the Covid-19.